A Critical Rreview of the book of “Ssociology and Eeducation” - Bizhan Zare (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present critique aims to review  form, content and techniques of the book entitled Sociology and Education based on theoretical fields and current scientificly accepted standards about the functions and desirable features of a University technical textbook. Findings of this research suggest that this book, in terms of criteria mentioned before, is of fairly good quality. Yet, it is necessary to add some issues in the field of methodology in Sociology of Education and create an enhanced social personality in students, social structure of education and so on to this book. Also, the inclusion of a summary of the important issues by asking questions to develop the thinking and searching of the audience and adding a list of new and upcoming books and resources related to the contents of each chapter at the end of the chapterss can add to the attractiveness and richness of the book's contents. In addition, it is necessary to devote part of the contents of each chapter to the present and future of the Iranian education.